Inappropriate doses of direct oral anticoagulants in real-world clinical practice: prevalence and associated factors. A subanalysis of the FANTASIIA Registry. Issue 10 (27th November 2017) - Ruiz Ortiz, Martín; Muñiz, Javier; Raña Míguez, Paula; Roldán, Inmaculada; Marín, Francisco; Asunción Esteve-Pastor, María; Cequier, Angel; Martínez-Sellés, Manuel; Bertomeu, Vicente; Anguita, Manuel; ,
Abstract: Aims: To describe the prevalence and associated factors of inappropriate doses of direct oral anticoagulants (DOAC) in a national registry of patients of real clinical practice. Methods and results : Five hundred and thirty outpatients with atrial fibrillation treated with DOAC were included in a prospective, national, multicentre study. The appropriateness of the doses of DOAC was defined according to the recommendations of the European Heart Rhythm Association. Mean age was 73 ± 9 years, with a 46% of women. Two hundred and sixty-seven patients were prescribed dabigatran, 190 rivaroxaban, and 73 apixaban. A total of 172 patients (32%) did not receive the appropriate dose: 93 patients received a lower dose (18%) and 79 patients a higher dose (15%). In the comparisons among the subgroups of inappropriately low, appropriate, and inappropriately high dose, we observed significant trends to older age (69 ± 8 years vs. 73 ± 10 years vs. 77 ± 6 years), more frequent female sex (37% vs. 46% vs. 59%), antiplatelet drugs (5% vs. 8% vs. 25%), rivaroxaban (14% vs. 38% vs. 53%), and apixaban use (5% vs. 15% vs. 19%), higher CHAD2 DS2 -VASc (3.00 ± 1.38 vs. 3.58 ± 1.67 vs. 4.59 ± 1.44) and HAS-BLED scores (1.83 ± 0.87 vs. 1.92 ± 1.07 vs. 2.47 ± 1.13), lower body mass index (30 ± 6 kg/m 2 vs. 29 ± 4 kg/m 2 vs. 28 ± 4 kg/m 2 ) and glomerular filtration rate (74 ± 27 mL/min vs. 70 ± 22 mL/min vs. 63 ± 16 mL/min), and lower frequency of dabigatran use (81% vs. 47% vs. 28%) (all comparisons P ≤ 0.01). Conclusion: In this real-life study, 32% of patients received an inappropriate dose of DOAC. Several clinical factors can identify patients at risk of this situation.